Application of recent advances in hydrodynamic methods for characterising mucins in solution - Almutairi, Fahad M.; Cifre, Jose-Gines Hernandez; Adams, Gary G.; Kök, M. Samil; Mackie, Alan R.; de la Torre, Jose Garcia; Harding, Stephen E. (Springer, 2016)
Mucins are the primary macromolecular component of mucus—nature’s natural lubricant—although they are poorly characterised heterogeneous substances. Recent advances in hydrodynamic methodology now offer the opportunity for gaining a better understanding of their solution properties. In this study a combination of such methods was used to provide increased understanding of a preparation of porcine intestinal mucin (PIM), MUC2 mucin, in terms of both heterogeneity and quantification of conformational flexibility. The new sedimentation equilibrium algorithm SEDFIT-MSTAR is applied to yield a weight average (over the whole distribution) molar mass of 7.1 × 106 g mol−1, in complete agreement with size exclusion chromatography coupled with multi-angle light scattering (SEC-MALS), which yielded a value of 7.2 × 106 g mol−1. Sedimentation velocity profiles show mucin to be very polydisperse, with a broad molar mass distribution obtained using the Extended Fujita algorithm, consistent with the elution profiles from SEC-MALS. On-line differential pressure viscometry coupled to the SEC-MALS was used to obtain the intrinsic viscosity [η] as a function of molar mass. These data combined with sedimentation coefficient data into the global conformation algorithm HYDFIT show that PIM has a flexible linear structure, with persistence length Lp ~10 nm and mass per unit length, ML ~2380 g mol−1 nm−1, consistent with a Wales-van Holde ratio of ~1.2 obtained from the concentration dependence of the sedimentation coefficient.